Pre-sorting method of complex system radar signals - Zeheng YUAN; Runlan TIAN; Xiaofeng WANG (Dianxin kexue)
The overall pulse parameters of complex system radar signals are varied and overlap seriously.The accuracy rate of the method using overall pulse parameter sorting is seriously decreased,but the intra pulse characteristic parameters are relatively stable.A method for pre-sorting radar signals in complex systems was proposed by extracting the phase coefficient of the intra-pulse characteristic parameters of the signal,combining the more stable inter-pulse parameters,and using the improved support vector clustering algorithm.Simulation results show that in the pre-sorting of complex system radar signals,the problem of increasing-batch can be solved effectively and the accuracy of sortingcan be improved.